In situ observations show vertical community structure of pelagic fauna in the eastern tropical North Atlantic off Cape Verde - H. J. T. Hoving (Nature Portfolio, 2020)
Abstract Distribution patterns of fragile gelatinous fauna in the open ocean remain scarcely documented. Using epi-and mesopelagic video transects in the eastern tropical North Atlantic, which features a mild but intensifying midwater oxygen minimum zone (OMZ), we established one of the first regional observations of diversity and abundance of large gelatinous zooplankton. We quantified the day and night vertical distribution of 46 taxa in relation to environmental conditions. While distribution may be driven by multiple factors, abundance peaks of individual taxa were observed in the OMZ core, both above and below the OMZ, only above, or only below the OMZ whereas some taxa did not have an obvious distribution pattern. In the eastern eropical North Atlantic, OMZ expansion in the course of global climate change may detrimentally impact taxa that avoid low oxygen concentrations (Beroe, doliolids), but favour taxa that occur in the OMZ (Lilyopsis, phaeodarians, Cydippida, Colobonema, Haliscera conica and Halitrephes) as their habitat volume might increase. While future efforts need to focus on physiology and taxonomy of pelagic fauna in the study region, our study presents biodiversity and distribution data for the regional epi- and mesopelagic zones of Cape Verde providing a regional baseline to monitor how climate change may impact the largest habitat on the planet, the deep pelagic realm.